Counterfeit Good Business in Oman. Does Any Factors Affect this Business? (Global Business Management Review (GBMR), 2022)
The illegal counterfeiting industry costs the global economy hundreds of billions of dollars every year. Through a descriptive approach, this article is trying to have an overlook on counterfeiting culture around the world and Gulf Countries in particular and little more details of its menace in Oman.The objective of the study is to explore the influencing factors behind the buying habits of counterfeit goods in Oman. As verity of factors that have an impact on customer’s intention to buy counterfeit products, this study focused on psychographic variables like; perceived risk, product attributes, integrity and socio-demographics variables; like education, age, income etc. The sample will be randomly targeted from a total population of 375 participates; who are located in north Al- Batenah region, Oman. The questionnaire were distributed as the following; (100) in Sohar, (120) in Saham, (80) in Liwa, and finally (100) in Shinas. The data analyzed by the help of SPSS 11 software using descriptive analysis (mean, Standard deviation, Variance) and Regression analysis. The study findings shows that people’s intention to purchase counterfeit products have positive impact in relation to the product attributes. Furthermore, the study concludes that there were a negative relationship between education, integrity, perceived risk and consumer’s intention to buy the counterfeit products. This study can help policy makers to know about ‘people perception’ on counterfeiting business and they can frame some policy initiatives to reduce the people’s purchase of counterfeits goods.